Effect of Postanthesis High Temperature on Grain Quality Formation for Wheat. (1st September 2017) - Liu, Leilei; Ma, Jifeng; Tian, Liying; Wang, Shenghao; Tang, Liang; Cao, Weixing; Zhu, Yan
Abstract : Core Ideas: High stress enhanced protein concentration, but reduced total starch concentration. High stress had more advantage effects on protein fractions at anthesis than 10 d after anthesis. High stress had significant negative effects on starch during grain filling. The combination stress did not have significant effects on protein fractions. The combination stress had significant effects on starch concentration. The protein and starch properties of wheat ( Triticum aestivum L.) are important factors for grain quality and these properties are documented to be influenced by temperatures. The present study was undertaken to investigate the effects of high temperature regimes, starting dates, durations and their combinations on grain protein and starch concentrations in two wheat cultivars Yangmai16 and Xumai30 with different heat tolerances. Four temperature regimes of 27/17°C, 31/21°C, 35/25°C, and 39/29°C were implemented for 3 and 6 d after anthesis and 10 d after anthesis. The concentrations of protein and starch components in grains were measured during the periods of postanthesis. High temperature enhanced both protein and amylose concentrations, but reduced amylopectin and total starch concentrations in grains. Higher concentration of protein fractions were observed when high temperatures were applied at anthesis than during the grain‐filling stage (10 d after anthesis). However, high temperatures during grain filling had profoundly more negative effects on starch concentration than at anthesis. The combination of high temperature regimes and durations did not have significant effects on the protein fractions, compared with either of the temperature regimes or durations applied individually, which was different from the starch concentration in response to the combination. Nevertheless, the combination of temperature regimes and durations could not cause more changes to grain starch concentrations than a single stress event.